Enhance Competitive Advantage For Recruitment System In Malaysia Through Improving Candidate Valuation Automation - Wong, Voon Yee (2010)
Hiring managers and human resource executive who actively involved in recruitment would undoubtedly find the application screening process as one of the most time consuming but necessary step, especially when there are many applications to sort through. It is very common for head hunters to go through hundreds of resume each day to search for suitable candidates to fill various vacancies to earn a living. With the rise of online recruitment portals in Malaysia in the late 1990s, the attraction and sourcing process has since been streamlined and achieved a significant speed up in comparison to spend weeks to get a vacancy advertisement posted on newspapers, and saving a lot of precious office space by storing resumes and applications on computers. However, due to the growth in job market and fast paced job application process, recruiters are now flooded with loads of applications on almost every hiring, although the potential yield is higher, it is harder for recruiters to cope with such huge amount of resumes without sacrificing some good candidates by not able to screen through all resumes. This research aims to find way to help busy human resource personnel in screening applications through the use of computerized system, suggesting possible solutions based on existing information system available, online recruitment job portals hence become the natural target with huge impact on the market as a whole. To encourage application screening automation without obvious financial reward would be the first problem to deal with, through several popular strategy planning frameworks and analysis I attempt to uncover benefits for online recruitment portals to embrace and welcome this initiative. And then follow up on gathering statistical data to identify important screening criteria and evaluate potential of using each criterion for auto screening and the risk to anticipate with such implementation. Throughout the end of this research, I believe implementing application screening automation tool for online recruitment portals could indeed build up competitive advantages, although it may not be a very long term advantage, it does raise the defence towards new entrants and substitution products with a feature that heavy users such as head hunters and expanding companies would be most benefited, and helping smaller companies to adopt better screening process, and this will too create customer loyalty. Last but not least, a list of recommendations is being provided to seed ideas for a challenging actual implementation of such feature and I am hopeful to see time and cost saving achievable through this practice.